CRITICAL REVIEW OF AL-GHAZALI'S SUFFICIENT THINKING AND ITS EXISTENCE IN INDONESIA - Abdul Hadi (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
In the digital information era such as today, where everyone can express their ideas, it is like a double-edged sword with a contradictory angle between positive and negative. Among the negative ones is the rampant doctrine of "truth and safety claims" that always appear amid society due to fanaticism for specific thoughts and sure scientists. This research seeks to reveal Ghazali's thoughts on alternatives in building Islamic epistemology with an "intuitive" method. Ghazali cannot fully accept the courage that is obtained through the way of "empiricism" and "rationalism" because he considers both of them deceptive. To reach the truth, he offers an integrative approach that unites reason and revelation on the one hand and between Sufism and Shari'a on the other. Ihya Ulum al-Din, the most significant work, Ghazali, is a concrete manifestation of this integrative thought, especially between fiqh and tasawuf (shari'a and essence). This work received a large audience and was widely accepted in the Islamic world, especially in Indonesia. Di era digital informasi sekarang ini dimana semua orang dapat mengepresikan gagasanya laksana pisau bermata dua dengan engle yang kontradiktif antara positiv dan negatif. Diantara sekian yang negatif adalah maraknya doktrin “klaim kebenaran dan keselamatan” selalu muncul ditengah-tengah masyarakat, karena kefantikan pada pemikiran tertentu dan ilmuwan tertentu pula. Penelitian ini berupaya untuk mengungkap pemikiran Ghazali dalam membangun epistemologi Islam dengan metode “intuisi” . Ghazali tidak dapat menerima sepenuhnya keberan yang diperoleh melalui pancaindera “empirisme”, juga akal “rasionalisme”, karena keduanya dianggapnya suka menipu. Dalam upaya meraih kebenaran, beliau menawarkan alternative pendekatan “integrative” yang menyatukan antara akal dan wahyu di satu pihak, dan antara tasawuf dan syariat di lain pihak. Karya tebesar Ghazali, Ihya Ulum al-Din, merupakan wujud nyata dari pemikiran integrative itu, khususnya antara fiqih dan tasawuf (syariat dan hakkekat). Karya ini mendapat aundiensi besar dan diterima secara luas di dunia Islam khususnya di Indonesia.